Pengaruh Religiusitas, Pelayanan Fiskus, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Di Cianjur - Jesica Anggreani Siringoringo; Lorina Siregar Sudjiman; Lenita Waty (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Taxpayer compliance is an important part of supporting tax revenues to increase. Analyzing the influence of religiosity, tax authorities services, and tax sanctions on individual taxpayer compliance. This research used primary data by distributing questionnaires at KPP Pratama Cianjur and using convenience sampling and obtained 60 respondents with the measurement method in this questionnaire using a Likert scale as the sample for this research. The results of this research show that partially religiosity does not have a positive and significant influence, but tax authorities' services and tax sanctions have a positive and significant influence on taxpayer compliance. Furthermore, simultaneously the influence of religiosity, tax authorities' services, and tax sanctions have a positive and significant influence on taxpayer compliance.